Hubungan perilaku kepala keluarga dengan pemberantasan sarang nyamuk demam berdarah dengue (PSN-DBD) - Fatwa Hidayat; Mindo Tua Siagian; Mido Ester Sitorus (Jurnal SAGO Gizi dan Kesehatan, 2021)
Background: The 3M Plus mosquito nest eradication movement is the most effective activity to prevent the occurrence of dengue disease and to realize environmental hygiene and healthy living behavior. The purpose of the 3M Plus mosquito nest eradication activity is to eradicate the breeding places of the Aedes mosquito through efforts to foster community participation so that dengue hemorrhagic fever (DHF) can be optimally prevented.Objective: The purpose of this study was to determine the relationship between the behavior of the head of the family with the implementation of eradicating the mosquito nests of dengue hemorrhagic fever.Method: This type of research uses a descriptive analytic approach with a cross sectional study design with a sampling technique using simple random sampling. The sample in this study were 73 heads of families from a population of 264 families. This research was conducted in March-September 2021. The data was collected by interview using a questionnaire, and supported by observational data. Data processing is carried out in a computerized manner starting with the stages of editing, coding, tabulating. Data analysis was performed bivariate (Chi-square test) and multivariate (Binary Logistics Regression) at 95% CI.Results: The results showed that there was a significant relationship between attitudes (p= 0.000) and the role of community leaders (p= 0.039) with the eradication of dengue mosquito nests. There was no relationship between knowledge (p= 0.767) and the eradication of dengue mosquito nests. The attitude variable is the dominant predictor of its relationship with the implementation of the eradication of dengue mosquito nests in Seunagan District, Nagan Raya Regency (Exp (B) = 7.2).Conclusion: There is a relationship between attitudes and the role of community leaders in eradicating dengue mosquito nests, but knowledge does not show a relationship. The success of eradicating dengue mosquito nests is dominated by the positive attitude of the local community.